A preliminary study of colorimetric nanoparticle evaluation of adulterated Simulated urine for amphetamine-type stimulants (ATS) abuse testing - Majeed, Masar Ibrahem (2023)
Drug abuse is a serious and widespread problem, and urine testing is considered one of the most used methods to detect drug abuse, but as evidenced by the history of people who have been referred to forensic laboratories, the use of cleaning powders, bases and their components, birth control pills, or aspirin pills to change Drug analysis results, because it is believed that these substances will affect the urine screening test, the purpose of this study is to determine the effect of these substances on common colorimetric laboratory tests (UDSTs) and to use colorimetric detection of unmodified gold nanoparticles to detect false negative results. In this study, a drug screening test strip (commonly performed on urine samples using immunoassays) will be screened using urine positive for amphetaminetype stimulants (ATS) and verifying the authenticity of the sample and the presence of ATS in the sample after addition of counterfeits using thin layer chromatography method. A method was used to screen false negative results with less effort and time than the thin layer chromatography (TLC) method using nanoparticle techniques of unmodified gold, the effect of eleven common types of adulteration was studied. Acetic acid, citric acid, hydroxide, hypochlorite based bleach, Pyridinium chorochromatic PCC, potassium dichromate, sodium chloride, ammonia and nitrate compounds, eye drops and detergents are the compounds discussed. In four tests, were tested on urine positive for ATS by adding adulterants at a 2:1 ratio, urine Dipstick testing and drug presence testing gave negative results for the adulteration cases, and a third colorimetric test was performed in the urine using TLC method, Marquis reagent, iodoplatins, and Dragendoff reagent. A silica plate was sprayed with a reagent for the virtual determination of amphetamine, methamphetamine, and 3,4- methylenedioxy-N-methamphetamine (MDMA) at a temperature higher than 20 °C as a result, false negative medications can be detected in the urine sample. But this method requires time, effort and materials, the fourth test is to use a nanoparticle detector formulated to detect the presence of amphetamine-type stimulants, by changing the colour from red to blue at a temperature of 24 degrees Celsius, the nanoparticle detector was able to detect the presence of amphetamine-type stimulants in low concentrations in urine samples, when compared the use of the TLC colorimetric detection method with the nanoparticle colorimetric detection method, we conclude that the latter is superior because it gives results in less time and requires less effort.